Telecommunications Performance, Reforms, and Governance - Estache, Antonio; Goicoechea, Ana; Manacorda, Marco (World Bank, Washington, DC, 2012)
The authors assess the effects of private capital and independent regulatory agencies on telecommunications performance by using cross-country panel data from 1990 to 2003. In general, they find that having independent regulatory agencies positively affects affordability and labor productivity, but negatively affects quality. Having private capital positively affects access, quality, and labor productivity, but negatively affects affordability. However, reform policies affect industrial and developing countries differently in some cases. The authors also find that governance plays an important role as it affects performance and interacts with reform policies.